Expanding Tactics for Listening. More Listening. More Testing. More Effective - Richards J. C. Jack (Oxford, Oxford University Press, 2011)
NEW FOR THE THIRD EDITION Four all-new, high-interest units Tactics for Testing section presents test-taking skills and practice tests for success on the TOEICH test and other exams. Downloadable audio files help students learn on the go. Conversation Corner in each unit provides Pronunciation and Dictation practice. CoMPONENTS Student Book Teacher's Book with Testing Program & Resource CD-ROM featuring: Unit quizzes Midterm and final tests in the style of the TOEIC® test and other exams Vocabulary and Conversation Worksheets providing unit-preview and expansion activities. Class Audio CDs. Audio Download Center.